2019
DOI: 10.1159/000500846
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sulforaphane on the Activity and Mineralization of Osteoblasts under Oxidative Stress

Abstract: Sulforaphane (SFN) is considered an antioxidant agent, but the biological effects on hypoxia-treated osteoblasts remain unclear. Therefore, the aims of this study were to investigate the effects of SFN on the activity and mineralization of osteoblasts in hypoxia. Osteoblasts were treated with hypoxia with or without SFN, and apoptosis was assayed with caspase 3 Activity Assay Kit and flow cytometer. The levels of reactive oxygen species (ROS) were measured with DCFH-DA. The levels of glutathione (GSH) and glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Yoon et al (14) previously demonstrated that SFN pretreatment protects against ischemia and reperfusion-induced acute renal failure in rats by suppressing oxidative stress in renal tissues. Furthermore, Chen et al (15) reported that SFN reduces ROS levels and protects osteoblasts from apoptosis in vitro, whilst Zhu et al (16) suggested that SFN prevents rat aortic smooth muscle cells death by inhibiting ROS production and oxidative cytotoxicity induced by xanthine oxidase. However, to the best of our knowledge, the potential effects of SFN on vascular endothelial cells under oxidative stress have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Yoon et al (14) previously demonstrated that SFN pretreatment protects against ischemia and reperfusion-induced acute renal failure in rats by suppressing oxidative stress in renal tissues. Furthermore, Chen et al (15) reported that SFN reduces ROS levels and protects osteoblasts from apoptosis in vitro, whilst Zhu et al (16) suggested that SFN prevents rat aortic smooth muscle cells death by inhibiting ROS production and oxidative cytotoxicity induced by xanthine oxidase. However, to the best of our knowledge, the potential effects of SFN on vascular endothelial cells under oxidative stress have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive ROS block and reduce the activity and differentiation of osteoblast, therefore inhibit the mineralization and osteogenesis [6]. Thus, using antioxidants for ROS scavenging benefits mineralization of osteoblasts [31].…”
Section: Mgo-pc Nps Enhanced the Mineralization Of Ecm In H 2 O 2 -In...mentioning
confidence: 99%